Particulate matter concentrations during winter seasons of 2016-2020 in Ulaanbaatar, Mongolia - Ganzorig Byambajav; Bayarmaa Batbaatar; Ariundelger Ariunsaikhan; Sonomdagva Chonokhuu (Proceedings of the Mongolian Academy of Sciences, 2021)
In this study, we have focused on the outdoor concentration of fine particulate matter (PM2.5) during the coldest months (November-February) of 2016-2019 and January-February of 2020 and illustrated the daily, monthly and quarterly averages according to the single-point measurement data collected by the PM2.5 sensor at an air quality monitoring station located in a central area of Ulaanbaatar. The study also analyzes monthly high, low, average and median points of PM2.5 concentrations in the area that was selected. The PM2.5 sensor collects its data at an interval of every ten seconds, registers 8500 data in one day and presents the concentration of fine particulate matter in micrograms per cubic meter (μg/m3). On the basis of data collection and analysis, from November through February of 2019-2020, average PM2.5 concentration dropped noticeably by 44 per cent compared to the previous years. The Government of Mongolia took immediate action to combat air pollution of Ulaanbaatar city in May 2019 by banning the burning of raw coal in the ger districts, which account for 70 per cent of the city’s emissions, and introduced coal briquette as the only type of fuel that was allowed to be burned in metal stoves as a primary source of heating and cooking. Our study reveals that the latest government regulation had a considerable impact on air quality during winter 2019-2020 and helped in the sudden decline of the most dangerous pollutant PM2.5 concentration very close to national standards (50 µg/m3 24-hour mean) within 6 months since the enforcement of the new regulation.